2012
DOI: 10.1007/s00264-012-1588-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for elective hip and knee arthroplasty: a multimodal thromboprophylaxis protocol

Abstract: Purpose Multimodal thromboprophylaxis includes preoperative thromboembolic risk stratification and autologous blood donation, surgery performed under regional anaesthesia, postoperative rapid mobilisation, use of pneumatic compression devices and chemoprophylaxis tailored to the patient's individual risk. We determined the 90-day rate of venous thromboembolism (VTE), other complications and mortality in patients who underwent primary elective hip and knee replacement surgery with multimodal thromboprophylaxis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 23 publications
(24 reference statements)
0
56
1
1
Order By: Relevance
“…Vulcano et al [40] reported that aspirin is a safe and effective way of preventing postoperative VTE events in low-risk patients with TJA. Hamilton et al [19] found that inpatient enoxaparin followed by outpatient aspirin in patients with standard VTE risk was an effective means of thromboprophylaxis after TJA.…”
Section: Discussionmentioning
confidence: 99%
“…Vulcano et al [40] reported that aspirin is a safe and effective way of preventing postoperative VTE events in low-risk patients with TJA. Hamilton et al [19] found that inpatient enoxaparin followed by outpatient aspirin in patients with standard VTE risk was an effective means of thromboprophylaxis after TJA.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were weight bearing as tolerated and received multimodal thromboprophylaxis [15]. Pharmacological thromboprophylaxis for six weeks included aspirin in patients with a low risk of thromboembolic disease and Coumadin in those who were high risk [15]. Patients were discharged to home or an inpatient rehabilitation unit within three to six days after surgery.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Rehabilitation was initiated on the day of surgery with a continuous passive motion (CPM) machine set from 0 to 60°. All patients were weight bearing as tolerated and received multimodal thromboprophylaxis [15]. Pharmacological thromboprophylaxis for six weeks included aspirin in patients with a low risk of thromboembolic disease and Coumadin in those who were high risk [15].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Sing and colleagues [10] As a result of these temporal trends, contemporary studies of 90-day mortality following TKA report rates in the range 0.14% to 0.31% [2,5,7,12]. It appears, therefore, that a more accurate estimate of 90-day mortality is approximately 0.2% or one in 500.…”
mentioning
confidence: 99%